Effect of Extrinsic and Intrinsic Motivation Factors to Employee Job Satisfaction in PT Nutrifood Indonesia in Surabaya - Kevin Ray Charano; Steven Harijanto (iBuss Management, 2015)
This study is accomplished to reveal what motivation factors affect employee job satisfaction in PT. Nutrifood Indonesia in Surabaya. Job satisfaction is an important factor that would determine employee performance and loyalty in the company. However, the researchers found out that there were many complaints from the employees in PT. Nutrifood Indonesia. Other than verbal confessions from the employees, low level of job satisfaction in the company might be revealed from the fact that the company suffered from a rather high employee turnover.At first, this research would measure through questionnaire spread to 40 employees in PT Nutrifood Indonesia to find out whether the employees are satisfied with the job or not, plus what intrinsic and extrinsic motivation factors that affect the job satisfaction itself. For the analysis, the researchers use multiple regression analysis since the analysis will involve two independent variables, affecting single dependent variable.The result of this research is showing that both extrinsic and intrinsic motivation factors significantly affecting employees’ job satisfaction in PT Nutrifood Indonesia in SurabayaKeywords: Working motivation, job satisfaction, human resource development